ANALYSIS ABILITY OF MATHEMATICAL CONNECTION OF SMP STUDENTS IN COMPARATIVE MATERIAL IN REVIEW OF GENDER DIFFERENCES - Lianawati, Indah; Purwasih, Ratni (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2018)
Mathematics is a science that can not be separated from other science as well as in everyday life. The ability of mathematical Connection aims to connect the mathematics with other disciplines and also daily life so that math can be more meaningful. This study aims to determine the ability of mathematical connections of junior high school students VIII class in one of junior high school in Bandung on Comparable material reviewed through gender. Subject consists of 35 students. In addition, the discussion on the mathematical connection ability for junior high school students from the difference of gender, between students and students in terms of ability penyimannya. The understanding of the mathematical connection capability rests on the concept of "socio-cultural construction" that there is a difference between men and women, resulting in their respective roles and duties. While based on the results of his research states that the difference of ability between male and female students and the results showed that the mathematical connection ability of female students is much better that is with an average of 3.71 from the students 3.59. In addition to gender factors are also found other factors that can affect the achievement of the ability of the connection of the readiness of students and teachers to learn, basic skills of students and basic knowledge of mathematical concepts